Clinical phenotyping of spondylodiscitis and isolated spinal epidural empyema: a 20-year experience and cohort study - Hijazi, Mido Max; Siepmann, Timo; El-Battrawy, Ibrahim; Glatte, Patrick; Eyüpoglu, Ilker; Schackert, Gabriele; Juratli, Tareq A.; Podlesek, Dino (Frontiers in Surgery, 2023)
Background: The incidence of spondylodiscitis (SD) and isolated spinal epidural empyema (ISEE) has been increasing in the last decades, but the distinct differences between both entities are poorly understood. We aimed to evaluate the clinical phenotypes and long-term outcomes of SD and ISEE in depth. Methods: We analysed data from our cohorts of SD and ISEE patients who were treated and assessed in detail for demographic, clinical, imaging, laboratory, and microbiologic characteristics at our center in Germany from 2002 to 2021. Results: We included 208 patients (72 females: age 75 [75 32-90] y vs. 136 males: 65 [23-87] y, median [interquartile range], p<0.001), of which 142 (68.3%) had SD and 66 (31.7%) had ISEE. Obesity was more common in ISEE than SD (ISEE: n=29, 43.9% vs. SD: n=37, 26.1%, p=0.016). However, there were no between-group differences in rates of diabetes and immunodeficiency. Methicillin-susceptible Staphylococcus aureus was the most frequent pathogen (n=100, 52.1%) and more common in ISEE (ISEE: n=43, 65.2% vs. SD: n=57, 40.1%, p=0.003). Skin infection was the most frequent primary source of infection in both entities (ISEE: n=14, 31.8% vs. SD: n=25, 24.8%, p=0.418). The most common surgical procedure in SD was instrumentation (n=87, 61%) and in ISEE abscess evacuation (n=63, 95%). Patients with ISEE displayed lower in-hospital complication rates compared to SD for sepsis (ISEE: n=12, 18.2% vs. SD: n=94, 66.2%, p<0.001), septic embolism (ISEE: n=4/48 cases, 8.3% vs. SD: n=52/117 cases, 44.4%, p<0.001), endocarditis (ISEE: n=1/52 cases, 1.9% vs. SD: n=23/125 cases, 18.4%, p=0.003), relapse rate (ISEE: n=4/46, 8.7% vs. SD: n=27/92, 29.3%, p=0.004), and disease-related mortality (ISEE: n=1, 1.5% vs. SD: n=11, 7.7%, p=0.108). Patients with SD showed prolonged length of hospital stay (ISEE: 22 [15, 30] d vs. SD: 38 [29, 53] d, p<0.001) and extended intensive care unit stay (ISEE: 0 [0, 4] d vs. SD: 3 [0, 12] d, p<0.002). Conclusions: Our 20-year experience and cohort analysis on the clinical management of SD and ISEE unveiled distinct clinical phenotypes and outcomes in both entities, with ISEE displaying a more favourable disease course with respect to complications, relapse rates, and disease-related mortality.